On the maximal terms of succesive Gelfond-Leont’ev-Salagen and Gelfond- Leont’ev-Ruscheweyh derivatives of a function analytic in the unit disc - M. M. Sheremeta (Математичні Студії)
For a function analytic in the unit disc the concepts of Gelfond-Leont'ev-Salagen and Gelfond-Leont'ev-Ruscheweyh derivatives of n-th order are introduced and the asymptotic behaviour of the maximal terms of their power development as n→+∞ is investigated.